Biological pest control in Mexican agriculture - Zelaya-Molina, Lily Xochilt; Chávez-Díaz, Ismael Fernando; de los Santos-Villalobos, Sergio; Cruz-Cárdenas, Carlos Iván; Ruíz-Ramírez, Santiago; Rojas-Anaya, Edith (Revista Mexicana de Ciencias Agrícolas, 2022)
Due to the continuous increase of the human population, the demand for food production should increase 70-100% in the following years. However, the food security of humanity is affected by several factors, among them pest insects, which are currently controlled through the application of large doses of synthetic insecticides, which generate serious problems in human health, resistance to pests, residues in foods, environmental pollution, outbreaks of secondary pests and reduction in populations of beneficial insects. Given this global scenario, these problems generate a greater demand for pest control methods that are efficient and environmentally friendly, so the objective of the present work was to address in a synthetic way the development and progress of research conducted in Mexico on the biological control of pest insects. This review focuses on technologies with a solid ecological basis for the gradual restoration of biodiversity lost in agroecosystems, so promising alternatives for pest control of great relevance in the Mexican countryside are addressed, such as the use of beneficial insects such as parasitoids, predators and entomopathogens that cause the death of pest insects, the use of sterile insect, bioinsecticides, such as microbial pesticides and other entomopathogens, incorporated plant protectors and biochemical pesticides. The demand for techniques related to the biological control of pest insects in Mexico should address the problems of transboundary, exotic, newly introduced pests and those pests that have remained for several decades in the country.